H.-G. Gadamer: The Problem of ‘Oblivion of Language’ and its Overcoming in the Hermeneutical Understanding of Meaning - Mickevičius, Arūnas (Problemos, 2025)
The aim of the article is to show how Hans-Georg Gadamer formulates the problem of the ‘Oblivion of language’ in Antiquity and how, in his search for the inner unity of word and thing, he sought to overcome this oblivion by using the scholastic treatment of verbum interius. Gadamer integrated the ‘inner word’ into his hermeneutic theory in order to overcome the ‘oblivion of language’ in antiquity. The article also shows how the Augustinian distinction between actus signatus and actus exercitus for Gadamer, discussed by Heidegger, opened up a hermeneutic approach to the ‘inner word’ that differs from the apophantics. The article argues that, in analyzing the ‘inner word’ and linguistic understanding, Gadamer emphasized two distinct but complementary aspects: on the one hand, the identity of thinking and its linguistic expression is emphasized, and the ‘inner word’ and its ‘external’ expression are inseparable; on the other hand, it is emphasized that we cannot, in verbal language (logos prophorikos), achieve full expression (logos endiathetos) of what we would like or be required to say in order to be adequately understood. Gadamer linked the lack of semantic fullness of the ‘external word’ to the experience of the Unvordenklichkeit. In order to explain the correlation between the inner and the outer word, the article interpretatively uses Husserl’s phenomenological attitude, which describes the way we know the meaning of some ‘thing’ as ‘thing in itself’ through different ‘profiles’. The ‘inner word’, mentioned by Gadamer in the phenomenological sense as ‘an object in itself’, is always given only in the expression of the ‘outer word’ as a partial profile and is incomplete in this respect. It is in no other way directly detectable, but only in the external expressions in which it opens. External expressions are not a defect of the full ‘inner word’, but are the only possible way or form of it, though not always perfect, and which may be expanded in the future. The different expressions of the external word referring to the partial meaning of the subject matter do not in any way provide for the relativization of the expressions themselves, because they all arise from the same ‘inner word’. But this identity of the ‘inner word’ is detected only in the difference of external expressions.